2009
DOI: 10.1128/jcm.01716-08
|View full text |Cite
|
Sign up to set email alerts
|

Value of Serial Quantification of Fungal DNA by a Real-Time PCR-Based Technique for Early Diagnosis of Invasive Aspergillosis in Patients with Febrile Neutropenia

Abstract: A study was designed to assess the reliability of the serial detection of Aspergillus sp. DNA to diagnose invasive aspergillosis (IA) in patients with febrile neutropenia. Two blood and two serum samples were taken weekly from 83 patients. A total of 2,244 samples were analyzed by real-time quantitative PCR. Twelve (14.4%) patients were diagnosed with IA. Taking two consecutive positive results as the diagnostic criterion, PCR detected 11 cases, with 4 false positives, giving sensitivity, specificity, positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
46
2
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 27 publications
(42 reference statements)
4
46
2
5
Order By: Relevance
“…The sensitivity of the method used in the present study was found to be 86.7%, which is higher than that in the previously mentioned study [12] but less than the 91.6% detected in another study [20]. This result might be due to examining more samples from each recipient or to the type of population in this study.…”
Section: Discussioncontrasting
confidence: 53%
“…The sensitivity of the method used in the present study was found to be 86.7%, which is higher than that in the previously mentioned study [12] but less than the 91.6% detected in another study [20]. This result might be due to examining more samples from each recipient or to the type of population in this study.…”
Section: Discussioncontrasting
confidence: 53%
“…We have previously described a RT-PCR assay which has a high sensitivity and specificity for the diagnosis of invasive aspergillosis (IA) in oncohematological patients when at least two blood samples are positive. 2 The low yield of the PCR technique in the study by Blennow et al could be because these authors used one PCR positive sample as the diagnostic criterion. Although, theoretically, the use of antifungal prophylaxis during the first 100 days after hematopoietic SCT may have contributed to reducing the sensitivity of DNA detection by PCR, as occurs with the detection of galactomannan (GM) Ag, 3 our data suggest that detection of DNAemia of Aspergillus sp.…”
mentioning
confidence: 85%
“…The specificity was generally lower, but could be significantly improved by establishing the requirement of two consecutive positive PCR results as a diagnostic criterion. 29,30 However, the diagnostic reliability of PCR assays in peripheral blood and serum specimens has been described to be rather limited. 31,32 The panfungal real-time PCR assay presented was specifically adapted to highly sensitive detection of fungal pathogens in peripheral blood or serum.…”
Section: Discussionmentioning
confidence: 99%